THE NYUGUH AGEUNG TRADITION OF GUMBAH HERITAGE KERIS AS A FORM OF IDENTITY FOR THE SUMEDANG LARANG PALACE - Kusmayati, Engkus; Permana, Cecep Eka (International Journal of Cultural and Social Science, 2025)
The Karaton Sumedang Larang is a traditional institution committed to preserving the cultural heritage of its ancestors. Among its annual rituals is ”The Nyuguh Ageng Ngumbah Keris Pusaka,” a ceremonial practice of cleansing sacred heirlooms, particularly keris and other regalia, from impurities such as dirt, stains, dust, and corrosion. The heirlooms purified (dikumbah) include the Pedang Ki Mastak, Keris Kidukun, Keris Panunggul Naga, Badik Curuk Aul I and II, Keris Nagasasra I and II, along with other sacred artifacts. This study employs a qualitative approach, with data collected through literature review, field observations, and interviews. The Nyuguh Ageng Ngumbah Keris Pusaka tradition represents an act of reverence toward the ancestors by safeguarding and maintaining their legacies. Furthermore, the keris as a cultural heirloom constitutes a distinctive feature of the Karaton Sumedang Larang, symbolizing its identity and cultural continuity.